Formation Of the Commissioner Judge Institution as A Court Supervision Policy (Judicial Scrutiny) Indonesian Criminal Justice System - Nurahman, Dwi; Maroni, Maroni; Fardiansyah, A. Irzal; Akib, Muhammad; Tisnanta, HS. (Yayasan Gema Bina Nusantara, 2024)
The idea of the concept of commissioner judges as Preliminary Examination Judge Institutions is the influence of the development of the times, as well as the ratification of the International Covenant on Civil and Political Rights by Indonesia, so that protection of the rights of suspects/defendants becomes the country's main priority in efforts to enforce the law through law enforcement officers. The fundamental function of Criminal Procedure Law is to seek material truth, so it is felt that the Preliminary Examination Judge as a new institution that emerged in the Criminal Procedure Code Bill is a new breakthrough to maintain the Due Process of Law so that it can continue to run according to expectations. It is also hoped that in the future there will be no innocent people who are sentenced without ignoring the interests of the victim. This scientific writing uses the Sociological Legal Research method (socio legal research).